Optimal cutting condition selection for high quality receptance measurements by sweep milling force excitation. (May 2022) - Franco, Oier; Beudaert, Xavier; Iglesias, Alex; Dombovari, Zoltan; Erkorkmaz, Kaan; Munoa, Jokin
Abstract: In large machine tool applications, where machine's productivity is limited by structural chatter vibrations, an accurate dynamic characterization is vital for predicting reliable stability lobes. Motivated by the fact that the sweep milling force excitation method shows a great potential, this paper conducts a numerical stability analysis for optimizing the tool radial engagement employed during the characterization cutting tests. Additionally, an alternative spectra computation technique is proposed which considerably improves the signal to noise ratio over the existing technique. The receptance measurement is demonstrated using time domain simulations and applied in a large-scale three axis machining centre obtaining more accurate stability boundary predictions. The source code of the temporal milling simulation and the sweep milling signal processing is freely available to reproduce the simulation and experimental results. https://github.com/OierFranco/SMFE . Graphical abstract: Image 1 Highlights: Machining system dynamics are identified through an improved Sweep Milling Force Excitation. Optimal tool radial engagement is selected based on numerical stability analysis. Analytical approximated expression for optimal tool radial engagement calculations are provided. High quality Frequency Response Functions of a three axis machining centre are experimentally characterized. Process stability limit prediction is improved by using characterized dynamic responses with respect to traditional impact hammer tests.